7x-3=5x+6-3

Simple and best practice solution for 7x-3=5x+6-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-3=5x+6-3 equation:


Simplifying
7x + -3 = 5x + 6 + -3

Reorder the terms:
-3 + 7x = 5x + 6 + -3

Reorder the terms:
-3 + 7x = 6 + -3 + 5x

Combine like terms: 6 + -3 = 3
-3 + 7x = 3 + 5x

Solving
-3 + 7x = 3 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-3 + 7x + -5x = 3 + 5x + -5x

Combine like terms: 7x + -5x = 2x
-3 + 2x = 3 + 5x + -5x

Combine like terms: 5x + -5x = 0
-3 + 2x = 3 + 0
-3 + 2x = 3

Add '3' to each side of the equation.
-3 + 3 + 2x = 3 + 3

Combine like terms: -3 + 3 = 0
0 + 2x = 3 + 3
2x = 3 + 3

Combine like terms: 3 + 3 = 6
2x = 6

Divide each side by '2'.
x = 3

Simplifying
x = 3

See similar equations:

| 41.2x+49.8-26.1x-30.1= | | T/0.3=1.7/0.9 | | 32-(30-4)= | | x+5x=500 | | -3/4xx=-27 | | 6+3u=12 | | 2/0.21=8-n | | 4t-24=28 | | 2x-8+6-x=4+10 | | 8/13=8/n | | 19/20x=36 | | 5(x-2)+2(x+5)= | | .25x-12=x+3 | | 70+60(8x+2)=180 | | 3x+42=9.5 | | 3(2x+1)-2(x+5)= | | (X-7/3)=9 | | 3-4(2-3x)=2(6x-2) | | Y=5y+6 | | 1/2z=15 | | 5z-3/4(8z-4)=-1 | | -2x-3+5x+2= | | 4ln(4x)+2=10 | | 7/10=m/4 | | -4K+2=-14 | | 3e^4x=1338 | | 5=4p-7 | | x-7/3=9 | | -4K+2=-12 | | 7x+4x+8x=0 | | -2a+20+9a=5a-8a | | 5=4b-7 |

Equations solver categories